Blood circulation values in patients with cardiac resynchronization therapy during the first 6 months in different stimulated QRS complex duration classes - Shanina, I.V.; Volkov, D.E.; Yabluchansky, N.I. (My University, 2015)
Twenty nine patients (10 — females, 19 — males) with obtained cardiac resynchronization therapy (CRT) treatment were examined at the department of ultrasound, clinical and instrumental diagnosis and minimally invasive technologies of SI «V.T. Zaitsev Institute of General and Emergency Surgery NAMS of Ukraine». Patients’ average age was 69±7 years. The frequency of ventricular rate of spontaneous and induced rhythm, systolic and diastolic blood pressure, left ventricular ejection fraction, end-diastolic and end-systolic volumes, interventricular septum, posterior wall thicknesses, left and right atriums, right ventricle sizes were evaluated before treatment, in the early postoperative period (the 3rd– 5th day) and 6 months after CRT-device implantation. Carefully executed CRT with high-quality selection of the electrode application point and adequate medical support can not only prevent the further extension, but also, in some cases, can shorten the duration of the extended baseline QRS complex with improving functional blood circulation values. CRT with high-quality selection of the electrode application point and adequate medical support is an effective treatment in patients with chronic heart failure.
Функціональні показники кровообігу у пацієнтів із кардіоресинхронізуючою терапією в перші 6 міс у різних класах тривалості стимульованого QRS-комплексу
Функциональные показатели кровообращения у пациентов с кардиоресинхронизирующей терапией в первые 6 мес в разных классах продолжительности стимулированного QRS-комплекса
Keywords: functional blood circulation values; cardiac resynchronization therapy; QRS complex duration